A Multimodal Analysis of the Makuku Diapers Commercial Video Featuring Nikita Willy - Rini Adriati; Frina Diniarta Nur; Lavenia Oktaviani (STIBA IEC JAKARTA, 2026)
Abstract: This study analyzes the multimodal aspects of the Makuku Diapers Commercial Video Featuring Nikita Willy. This study uses a qualitative method to examine five modes of multimodality: linguistics, visual, gestural, spatial, and audio. The data for this research was gathered from the commercial video on the YouTube channel. The study applies the theory of Kress and van Leeuwen (2001, as cited in Discourse Analyzer, 2024) to identify the semiotic signs in the commercial video. Kress and van Leeuwen's (2001) theory is used to analyze the linguistic mode, while the theories of van Leeuwen (2006, 2001, and 1999) are used for the visual mode. McNeill's (1992) theory is applied to the gestural mode. The spatial mode is analyzed using the theories of van Leeuwen (2006) and Kress and van Leeuwen (1996), and van Leeuwen's (1999) theory is used for the audio mode. Additionally, the study employs a three-point Likert scale (Likert, 1932)—Effective, Somewhat Effective, and Ineffective—to assess the effectiveness of the modes and their aspects in the commercial video. Findings indicate that all five modes of multimodality are present and effectively utilized in the commercial, with the visual mode being the most successfully executed.